Testicular Biometry, Body-weight, Seminal Attributes and their Correlations in Murrah Bulls - Saurabh,; Srivastava, Sushant; Singh, Bhoopendra; Alam, Kabir; Kumar, Rajesh; Kumar, Rabindra; Sharma , Pushkar (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was carried out to evaluate the testicular markers and their correlations with body-weight and seminal output in Murrah  bulls. Semen samples were collected from eight Murrah buffalo bulls, aged 4 to 8 years, maintained at the bull station of deep-frozen  semen lab of Veterinary College, Faizabad (Uttar Pradesh), India. Biometrical (scrotal circumference, testicular length, testicular diameter,  and testicular volume) evaluation was performed by Vernier caliper and scrotal tape in all experimental bulls. The overall mean (± SE)  body-weight, scrotal circumference, right testicular length, left testicular length, right testicular diameter, left testicular diameter,  pooled testicular volume, ejaculate volume, sperm concentration, and sperm count per ejaculate of Murrah bulls were 716.5 ± 0.59 kg,  34.37 ± 0.41 cm, 11.85 ± 0.12 cm, 12.32 ± 0.14 cm, 7.81 ± 0.07 cm, 8.26 ± 0.08 cm, 791.4 ± 22.62 cm3, 3.82 ± 0.12 mL, 1271 ± 22.68 million/mL,  and 4852 ± 166.3 million with significant differences (p
Keywords: Body-weight; Ejaculate volume; Murrah bull; Sperm output; Testes; Testicular volume